Respuesta :
The rule for division of similar bases with exponents is:
(a^b)/(a^c)=a^(b-c)
In this case we have:
(3^-9)/(3^-12)
3^(-9--12)
3^3
27
(a^b)/(a^c)=a^(b-c)
In this case we have:
(3^-9)/(3^-12)
3^(-9--12)
3^3
27
The Simplified form of 3^-9/3^-12 is mathematically given as
x=27
What is the Simplified form of 3^-9/3^-12?
Question Parameter(s):
Simplify 3^-9/3^-12
Generally, the equation for the expression is mathematically given as
( 3^{-9})/(3^{-12})
Therefore
using law of indices
x=3^(-9-(-12)
x=3^3
x=27
In conclusion, the Simplified form of 3^-9/3^-12
x=27
Read more about Arithmetic
https://brainly.com/question/22568180
#SPJ2